Interferon-γ-inducible protein 16 (IFI16) is required for the maintenance of Epstein-Barr virus latency - Gina Pisano; Arunava Roy; Mairaj Ahmed Ansari; Binod Kumar; Leela Chikoti; Bala Chandran (Virology Journal, 2017)
Abstract Background Epstein-Barr virus (EBV) exhibits both lytic and latent (Lat. I, II, and III) phases in an infected individual. It’s during the latent phase of EBV that all EBV-associated cancers, including Burkitt’s lymphoma, nasopharyngeal carcinoma and lymphoproliferative disease arise. Interferon-γ-inducible protein 16 (IFI16) is a well-established innate immune sensor and viral transcriptional regulator involved in response to invading DNA viruses. During latency, IFI16 remains in the nucleus, in part bound to the EBV genome; however, neither its role in EBV lytic cycle or latency has been established. Methods Short interfering RNA against IFI16 and IFI16 overexpression were used to identify the role of IFI16 in the maintenance of EBV latency I. We also studied how induction of the lytic cycle affected IFI16 using the EBV positive, latently infected Akata or MUTU-1 cell lines. Akata cells were induced with TPA and MUTU-1 cells with TGF-β up to 96 h and changes in IFI16 protein were analyzed by Western blotting and immunofluorescence microscopy. To assess the mechanism of IFI16 decrease, EBV DNA replication and late lytic transcripts were blocked using the viral DNA polymerase inhibitor phosphonoacetic acid. Results Knockdown of IFI16 mRNA by siRNA resulted in enhanced levels of EBV lytic gene expression from all temporal gene classes, as well as an increase in the total EBV genome abundance, whereas overexpression of exogenous IFI16 reversed these effects. Furthermore, 96 h after induction of the lytic cycle with either TPA (Akata) or TGF-β (MUTU-1), IFI16 protein levels decreased up to 80% as compared to the EBV-negative cell line BJAB. Reduction in IFI16 was observed in cells expressing EBV lytic envelope glycoprotein. The decreased levels of IFI16 protein do not appear to be dependent on late lytic transcripts of EBV but suggest involvement of the immediate early, early, or a combination of both gene classes. Conclusions Reduction of IFI16 protein levels following lytic cycle induction, as well as reactivation from latency after IFI16 mRNA knockdown suggests that IFI16 is crucial for the maintenance of EBV latency. More importantly, these results identify IFI16 as a unique host factor protein involved in the EBV lifecycle, making it a potential therapeutic target to combat EBV-related malignancies.